Global Change and the Challenges of Sustainably Feeding a Growing Planet - Hertel, Thomas W.; Baldos, Uris Lantz C. (Springer International Publishing : Imprint: Springer, 2016)
This book explores the fundamental determinants of sustainability as seen through the lens of long term changes in agricultural land use and the associated implications for environmental and food security. Each chapter builds part of the global sustainability story by focusing on one driver, or underlying determinant, of land use change at global scale. It starts with key factors which have been influential in the past, such as growth in population, incomes and agricultural productivity, thereafter turning to new drivers such as biofuels, climate change and demand for environmental services. Specialized topics include food security outcomes, projections of future agricultural prices, greenhouse gas emissions, the role of globalization and market integration. The final chapter integrates all of these elements into a comprehensive analysis of food and environmental security in 2050. The book draws heavily on the emerging body of literature on these topics, summarizes key findings and organizes these within a unifying economic framework.